(untitled) (Heritage, 2023)
Civil wars in former Yugoslavia have resulted in divided societies especially in those cultures where ethnic and sectarian divisions exist. Problems become intergenerational when there are not sufficient resolutions leading to viable reconciliation. There often exists a collective malaise in these situations that manifests itself as primary and secondary post-traumatic disorders (PTSD). Secondary PTSD often afflicts the children and adolescent off springs of their parents or grandparents impacted by the conflict per se. Given that, group profiles of students from Republika Srpska (2010. versus 2020.) measured with the Problem-Oriented Screening Instrument for Teenagers, POSIT (Rahdert 1991) which covers 10 functional adolescent problem areas including substance use, mental health, family relations, and aggressive behavior/delinquency. Тen years later, it is important to maintain focus on the unmet psychological and social/cultural needs of traumatized children and youth, second-generation war victims because neglecting these problems could be costly for society in terms of later disorganization of this population, as it matures.